Presentation an internal control quality prediction model for companies listed in Tehran Stock Exchange - Saeed Alipour; Asgar Pakmaram; Rasol Abdi; Jamal Bahri sales (فصلنامه بورس اوراق بهادار, 2020)
Conflict of interests between managers and employees paves the way for the improper conduction of internal controls, thus obscuring the realization of the goals expected of the implementation of such controls. Therefore, it is highly necessary to work out a tool or a process to examine and evaluate the efficiency of these controls. Allied to this, the present study sought to present an internal control quality prediction model for companies listed in Tehran Stock Exchange. To do so, 141 out of all companies listed in Tehran Stock Exchange were selected for the 2012-2017 timeframe. The research hypotheses were tested via the compositional data analysis. The results showed that a model based on the characteristics of economic units could detect the units with weak internal controls. The auditors’ characteristics were also shown to affect the identification and reporting of such units with weaknesses in their internal controls. There is a significant relationship between the measurement indexes of the goals expected of the implementation of internal controls and economic units with weakness in their internal controls.